119k views
3 votes
Beth solved the system of equations by making a substitution for y in the second equation.

What equation did she get as a result of that substitution?

y = 4x – 11
3x + 5y = –9





12x – 11 = –9

12x – 55 = –9

3x + 20x – 55 = –9

3x + 20x – 11 = –9

1 Answer

6 votes
When Beth made the substitution, she got
3x +5(4x -11) = -9
After using the distributive property to eliminate parentheses, her equation was

3x +20x -55 = -9 . . . . . . . . . . matches the 3rd selection
User Anupam Gupta
by
5.1k points